Uniform Statistical Convergence on Time Scales - Altin, Yavuz; Koyunbakan, Hikmet; Yilmaz, Emrah (Hindawi Ltd, 2014)
We will introduce the concept of m- and (lambda, m)-uniform density of a set and m- and (lambda, m)-uniform statistical convergence on an arbitrary time scale. However, we will define m-uniform Cauchy function on a time scale. Furthermore, some relations about these new notions are also obtained.
Keywords: Integration